Review of Child Consumer Protection in the Practice of Online Gambling Games Through the Gacha System - Fibrianti, Nurul; Dahlan, Tri Andari; Anitasari, Rahayu Fery; Paramita, Niken Diah; Putra, Tegar Islami (The Indonesian Journal of International Clinical Legal Education, 2024)
The online game industry is increasingly widespread and diverse in its practices to attract users, one of which is the use of the gacha system. This article discusses the gacha system in online games and its potential impact on children. Gacha, which involves paying for random in-game items, is often compared to gambling due to its elements of chance and the potential for profit. The system triggers dopamine release, making players feel pleasure, but children are particularly vulnerable to its mechanics. The article highlights the lack of juridical protection in Indonesia against online games that use gacha systems. While the Child Protection Law prohibits the economic exploitation of children, there are no specific regulations addressing gacha systems in online games. The authors identify the potential economic exploitation of children through gacha as a significant problem. They suggest two solutions: promoting traditional games with character-building content for children, and providing education on character development when introducing these games. From a legal perspective, the article calls for concrete protection measures for children playing online games with gacha systems. The research uses a normative juridical approach, employing library research based on literature.